Seychelles : Request for a Three-Year Policy Coordination Instrument and Ex-Post Assessment of Longer-Term Program Engagement-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Seychelles' Request for a Three-Year Policy Coordination Instrument (PCI) and Ex Post Assessment of Longer-Term Program Engagement. The PCI for Seychelles will build on the lessons from the previous programs supported by the IMF. It aims to support the authorities' efforts to consolidate macroeconomic stabilization and foster sustained and inclusive growth. While the PCI involves no use of IMF resources, successful completion of program reviews would help signal Seychelles' commitment to continued strong economic policies and structural reforms. Risks to the program are considered moderate given Seychelles' impressive track record under the successive IMF arrangements. The IMF staff support the authorities' request for a PCI.